Fabrication of two-dimensional Ti3C2Tx MXenes by ball milling pretreatment and mild etchant and their microstructure. Issue 18 (15th December 2020) - Tian, Shen; Cheng, Guojun; Tang, Zhongfeng; Sha, Feixiang; Xuan, Ziyue; Ding, Guoxin
Abstract: 2D transition metal carbide/nitride have demonstrated wide application potential in energy storage and composites. In this article, a kind of 2D sheet structures of Ti3 C2 Tx MXenes were prepared through ball milling pretreatment, followed by mild etching with HCl and LiF. After ball grinding, the size of Ti3 AlC2 was uniform and D50 decreases from 4.488 μm to 1.454 μm, which is conducive to the preparation of MXenes Ti3 C2 Tx with a well-defined 2D sheet structure. The microstructure of the Ti3 C2 Tx was analyzed by X-ray diffraction (XRD) and scanning electron microscopy. Results of XRD showed that the (002) peak of Ti3 AlC2 broadened and shifted from 2θ = 9.82° to 2θ = 6.63°. The corresponding interlayer distance was increased from 8.99 Å to 13.32 Å. The Ti3 C2 Tx MXenes phase were uniform and showed a "Tyndall effect". Obvious "accordion-like" structures were formed in Ti3 C2 Tx MXenes, which could achieve the etching effect of the hydrofluoric acid method. The thermogravimetric results showed that Ti3 C2 Tx MXenes phase prepared by this method absorbed many functional groups on the surface and had a high weight loss rate of 38.2%. All results demonstrated that the obtained Ti3 C2 Tx MXenes by HCl and LiF etchant via ball milling pretreatment has not only a well-defined 2D sheet structure, but also good dispersion stability and thermal stability. This article provides a new idea for the preparation of Ti3 C2 Tx MXenes phase.